2023
DOI: 10.1111/beer.12524
|View full text |Cite
|
Sign up to set email alerts
|

Board gender diversity, government subsidies, and green vehicles sales: Evidence from China

Abstract: Environmental sustainability has emerged as a driver in policy formulation and business operations because of consumer demand and environmental concerns. Consumer behaviors have changed and have led to demand for products such as electric vehicles (EVs), which are less harmful to the environment than vehicles powered by combustible gas engines. Government subsidies play a vital role in developing green technology in emerging industries (Jung & Feng, 2020). Policymakers have supported this emerging industry by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 111 publications
(176 reference statements)
0
2
0
Order By: Relevance
“…Financial subsidies are one such cue that can positively influence behavior by providing an external motivation to engage in certain activities. Specifically, previous literature found that the subsidies provide a tangible financial benefit to firms that engage in environmentally friendly behavior, and this financial incentive can serve as a motivator for firms to prioritize and invest in environmental activities (Dong et al, 2019; Singh et al, 2023; Wu et al, 2020). Such financial reward for behavior is a kind of positive behavior cue, which can become the external motivation for firms to engage in certain activities.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Financial subsidies are one such cue that can positively influence behavior by providing an external motivation to engage in certain activities. Specifically, previous literature found that the subsidies provide a tangible financial benefit to firms that engage in environmentally friendly behavior, and this financial incentive can serve as a motivator for firms to prioritize and invest in environmental activities (Dong et al, 2019; Singh et al, 2023; Wu et al, 2020). Such financial reward for behavior is a kind of positive behavior cue, which can become the external motivation for firms to engage in certain activities.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…In addition, antecedent elements that affect consumers' behavioral intention to buy electric vehicles (EVs) include environmental concerns and perceptions of environmental legislation (Zang et al, 2022). The notion of perceived endorsement, encompassing perceived benefit, perceived risk, range anxiety, and attitude, provides additional insight into consumers' intents to acquire electric vehicles (EVs) (Singh et al, 2023). Policymakers and industry players are actively involved in supporting the use of EVs as the EV market continues to develop.…”
Section: Introductionmentioning
confidence: 99%